2010
DOI: 10.5114/aoms.2010.13512
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia in the developing countries: the Iranian experience

Abstract: IntroductionManagement of haemophilia and inherited bleeding disorders is a major challenge especially in developing countries, because of a shortage or absence of products, the cost and the infrastructural health problems. Development of local expertise which results in an improved outlook and reduction in mortality and morbidity in these countries can be helpful for advocators in other developing countries. However, very little information on demography and organizational models for haemophilia care in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
(36 reference statements)
1
17
1
Order By: Relevance
“…6,8,10 Studies from other parts of world shows a higher prevalence ranging from 24-30%. 6,9,11,12 Keeping these facts in mind it is necessary to identify patients with inhibitors and provide treatment facilities to them so these patients can lead a productive life because management of Hemophilia patients with inhibitor is very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10 Studies from other parts of world shows a higher prevalence ranging from 24-30%. 6,9,11,12 Keeping these facts in mind it is necessary to identify patients with inhibitors and provide treatment facilities to them so these patients can lead a productive life because management of Hemophilia patients with inhibitor is very difficult.…”
Section: Discussionmentioning
confidence: 99%
“…They are characterized by intra-articular bleeding which leads to severe arthropathy [1]. Haemophilia A and B have been associated with increased incidence of bone disease (osteopenia or osteoporosis), about 67-86% in a few studies [2–6].…”
Section: Introductionmentioning
confidence: 99%
“…of their patients were HCV positive and none of them had serological evidences of hepatitis B virus, and also with Eshghi et al [12] who represented in his work the prevalence of HCV infections among studied hemophilic patients was 15.6% and prevalence of HBV was 8%.This can be explained by the increased awareness and use of safe virus inactivated plasma transfusions and factor concentrates. The current study showed that, the most common line of treatment used in our hemophilic patients was on demand factor concentrate treatment used by 54 patients representing 72% of studied group and prophylaxis treatment used by 18 patients representing 24% of studied group and only 3 patients were without treatment representing 4%.…”
Section: Discussionmentioning
confidence: 64%